Pengenalan Dunia Coding: Pelatihan Dasar Pemrograman Bagi Siswa SMA Negeri 5 Surabaya - Titik Lusiani; Didit Anindita; Agus Dwi Churniawan; Sulistiowati; Ayouvi Poerna Wardhanie (Jurnal Ragam Pengabdian, 2025)
In this digital era, programming skills are fundamental, but high school curriculums often do not accommodate this need in depth. Realizing this gap, a Community Service activity entitled "Introduction to the World of Coding: Basic Programming Training for Students of SMA Negeri 5 Surabaya" was carried out. This training aims to equip students with basic programming knowledge and skills to prepare them for digital challenges. The implementation method is divided into three stages: pre-implementation, implementation, and evaluation. The pre-implementation stage includes identifying partner needs, formulating materials (Python as a programming language), and preparing a schedule of four meetings in November-December 2024. The implementation was carried out offline with an interactive direct instruction method, including material explanations, direct practice, discussions, and assignments. The evaluation results showed the effectiveness of the training. Based on the satisfaction questionnaire using the Likert scale (Parasuraman), the overall average reached 4.76 (out of 5), indicating that participants strongly agreed with the implementation of the training. The aspects of reliability (4.83) and responsiveness (4.80) received the highest scores. This shows that this basic programming training has succeeded in increasing the interest and insight of students of SMA Negeri 5 Surabaya in the world of coding.